Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.3892/or.17.3.617
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of glycyrrhizin on estrogen-related endometrial carcinogenesis in mice

Abstract: Abstract. We have previously reported on the inhibitory effect of Glycyrrhizae radix (Gl radix) on mouse endometrial carcinogenesis. The present study was performed to clarify the effects of Gl radix and glycyrrhizin (GL), the main part of Gl radix, on estradiol (E 2 )-related endometrial carcinogenesis. Both Gl radix and GL exerted a significant decrease in the COX-2, IL-1· and TNF-· mRNA expressions. GL generated a significant decrease in the incidence of endometrial adenocarcinoma. Accordingly, the preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Researchers have also shown that Gc or GA reduced melanoma cell proliferation [31] and metastasis [32]. Other cancers that have been reported to be sensitive to the antiproliferative effects of GA or Gc include UVB-induced skin carcinogenesis [33•], prostate cancer [34], stomach cancer and leukemia [35,36], gastric cancer [37], endometrial carcinogenesis [38], pituitary adenomas [39], and breast cancer [40]. GA was reported to suppress A549 and NCI-H460 non-small cell lung cancer (NSCLC) growth and inhibit thromboxane synthase activity [41].…”
Section: Glycyrrhizin and Glycyrrhetic Acidmentioning
confidence: 99%
“…Researchers have also shown that Gc or GA reduced melanoma cell proliferation [31] and metastasis [32]. Other cancers that have been reported to be sensitive to the antiproliferative effects of GA or Gc include UVB-induced skin carcinogenesis [33•], prostate cancer [34], stomach cancer and leukemia [35,36], gastric cancer [37], endometrial carcinogenesis [38], pituitary adenomas [39], and breast cancer [40]. GA was reported to suppress A549 and NCI-H460 non-small cell lung cancer (NSCLC) growth and inhibit thromboxane synthase activity [41].…”
Section: Glycyrrhizin and Glycyrrhetic Acidmentioning
confidence: 99%
“…The major active component of licorice root is glycyrrhizin, an oleanane-type triterpene saponin which constitutes 2-24% of total dry weight (7). Glycyrrhizin is extensively reported to have several pharmacological activities including anti-inflammatory (8), immunomodulatory (9), antiulcer (10) and anti-tumorigenic activities (11,12). Glycyrrhizin also has antiviral activity against hepatitis B virus, HIV (13,14) and severe acute respiratory syndrome (SARS)-associated coronavirus (15).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, administration of licorice extracts had anti-nephritic properties [13,14], which were linked to its free radical scavenging properties. Furthermore, licorice may suppress estrogen-induced c-fos/jun expressions and decrease the incidences of uterine endometrial atypical hyperplastic and malignant lesions in mice [15]. However, there is no mechanistic support for most of the other effects claimed for licorice.…”
mentioning
confidence: 92%